Selectivity of clomazone and S-metolachlor applied after cassava pruning - Costa,N.V. (2013)
The objective of this work was to evaluate the selectivity of clomazone in two formulations and S-metolachlor applied on shoots of different sizes after pruning of 'Baianinha' cassava. The experiment was arranged in a randomized block design in a factorial 5 x 2 (5 treatments x 2 sizes of shoots after pruning - 10 and 33 cm) with four replications. The herbicides evaluated were: clomazone (encapsulated suspension - 900 g h-1), clomazone (encapsulated suspension - 1,080 g ha-1), clomazone (emulsifiable concentrate 900 g ha-1), S-metolachlor (1,920 g ha-1) and an untreated control. During the experiment, all plots were kept free of weed interference by hand weeding. It was concluded that both the formulations of clomazone and S-metolachlor were selective when applied on both the shoot sizes evaluated. However, the application of S-metolachlor on 33 cm shoots gave higher selectivity to 'Baianinha' cassava plants.